PELATIHAN KEWIRAUSAHAAN MEMBUAT ANEKA PRODUK PASTRY DAN BAKERY UNTUK SISWA SMA NEGERI 2 DENPASAR - Ida Bagus Ketut Soma Antara; Luh Eka Susanti; A.A.Ayu Arun Arianti; I Wayan Eka Sudarmawan; Ni Wayan Astri Utami (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The Covid-19 pandemic has had a significant impact on the economy of people from various circles. One of the impacts is on the world of education, where the Covid-19 pandemic has reduced the economic conditions of parents of students. Thus, many students are unable to continue their education from high school to college because of financial constraints. For high school students, continuing their education to college is one of the main needs. This is because high school graduates are not equipped with special skills while studying at school, in contrast to vocational graduates. Seeing these conditions, SMA Negeri 2 Denpasar cooperated with IPB International to provide training in the field of pastry and bakery for their students. This field was chosen because currently there are many cake and bakery shops popping up, so it is hoped that the participants who take part in the training can later become one of the actors in the industry. The collaboration between Denpasar 2 Public High School and IPB International will later provide training on making various processed cakes and breads, product packaging, and marketing. The activity will be carried out in four meetings, with a duration of five and four hours in each meeting. The training material will be delivered by IPB International kitchen instructors who have specific skills in the field of cake and bread processing. The output targets that will be achieved through this service are 1) Increasing human resources, 2) scientific articles published in national journals, 3) publication of articles in print media, and 4) activity videos uploaded via the IPB International Youtube channel. The additional output target is the monograph of the results of dedication